A retrospective multicenter study of carbon‐ion radiotherapy for major salivary gland carcinomas: Subanalysis of J‐CROS 1402 HN. Issue 5 (27th April 2018) - Hayashi, Kazuhiko; Koto, Masashi; Demizu, Yusuke; Saitoh, Jun‐ichi; Suefuji, Hiroaki; Okimoto, Tomoaki; Ohno, Tatsuya; Shioyama, Yoshiyuki; Takagi, Ryo; Ikawa, Hiroaki; Nemoto, Kenji; Nakano, Takashi; et al.
Abstract : A retrospective multicenter study was carried out to assess the clinical outcomes of carbon‐ion radiotherapy for head and neck malignancies (Japan Carbon‐Ion Radiation Oncology Study Group [J‐CROS] study: 1402 HN). We evaluated the safety and efficacy of carbon‐ion radiotherapy in patients with major salivary gland carcinoma. Sixty‐nine patients treated with carbon‐ion radiotherapy at four Japanese institutions were analyzed. Thirty‐three patients (48%) had adenoid cystic carcinomas, 10 (14%) had mucoepidermoid carcinomas, and 26 (38%) had other disease types. Three patients (4%) had T1 disease, 8 (12%) had T2, 25 (36%) had T3, and 33 (48%) had T4. The median radiation dose was 64 Gy (relative biological effectiveness) in 16 fractions. The median gross tumor volume was 27 mL. The median follow‐up period was 32.7 months. The 3‐year local control rate and overall survival rate were 81% and 94%, respectively. Regarding acute toxicities, seven patients had grade 3 mucositis and seven had grade 3 dermatitis. Regarding late toxicities, one patient had grade 3 dysphagia and one had a grade 3 brain abscess. No grade 4 or worse late reactions were observed. In conclusion, definitive carbon‐ion radiotherapy was effective with acceptable toxicity for major salivary gland carcinomas.